Studies on The Performance of Some Varieties of Pulse Crops on Drylands of Western Rajasthan - Prasad, M V R; Chaudhary, B S (Annals of Arid Zone, 2016)
An evaluation of a wide range of varieties of green gram and cowpeas on drylands indicated that early maturing varieties with compact plant type and higher number of pods per plant such as S8 of mung and FS68 and K I I of cowpeas showed a consistently superior performance than the others.